Surgical Efficacy and Safety of Patients with Locally Advanced Gastric Cancer following Neoadjuvant Concurrent Chemoradiotherapy and Chemotherapy. (19th March 2022) - Li, Ching-Chun; Yeh, Yung-Sung; Chen, Yen-Cheng; Su, Wei-Chih; Chang, Tsung-Kun; Tsai, Hsiang-Lin; Huang, Ching-Wen; Ma, Cheng-Jen; Yin, Tzu-Chieh; Chen, Po-Jung; Wang, Jaw-Yuan
Abstract : Background . The safety and efficacy of gastrectomy for locally advanced gastric cancer (LAGC) following neoadjuvant therapy have gained increasing attention. In this article, we present our preliminary treatment results and compare the surgical safety and outcomes of neoadjuvant concurrent chemoradiotherapy (CCRT) with those of chemotherapy in patients with LAGC. Patients and Methods . Sixty-three patients with a diagnosis of LAGC (clinical staging cT3N2+, cT4aN+, or cT4b) who had received neoadjuvant therapy at any period from January 2014 to December 2020 were enrolled. Among 63 patients who received neoadjuvant therapy, 38 were treated with CCRT and 25 were treated with chemotherapy. They regularly received follow-up until July 2021. The patients' characteristics, including their clinical data, perioperative results, and pathologic outcomes, were analyzed. Results . The CCRT and chemotherapy groups did not significantly differ with respect to age, sex, or clinical stage (all p > 0.05 ). Finally, radical gastrectomy was performed in 15 (39.5%) patients with neoadjuvant CCRT and 10 (40.0%) patients with neoadjuvant chemotherapy. Both groups did not significantly differ with respect to operation time, blood loss, operative morbidities, or postoperative length of stay (both p > 0.05 ). The patients in the CCRT group exhibited favorable pathologic responses after treatment: three patients exhibited a pathologic complete response (pCR) and four, seven, and one patients exhibited a response at pathologic stages I, II, and III, respectively. By contrast, among the patients in the chemotherapy group after treatment, one patient exhibited a pCR and one, four, and four patients exhibited a response at pathologic stages I, II, and III, respectively. Conclusions . Radical resection in patients with LAGC is challenging. This study reports that neoadjuvant CCRT is associated with better pathologic response with no increase in serious postoperative complications. However, further prospective randomized trials involving patients with LAGC receiving neoadjuvant CCRT should be conducted to verify the findings of this retrospective study.